Minyak Atsiri Daun Jeruk Purut (Citrus Hystrix) Sebagai Disinfektan Untuk Menurunkan Angka Kuman Meja Makan - Siti Arwini, Dhea Nofita; Istiqomah, Siti Hani; Muryani, Sri (Jurnal Kesehatan Lingkungan Mapaccing, 2025)
Restaurants can potentially cause health problems or illness, even food poisoning. Restaurants have tables where food is served. Bacterial contamination can be caused by improper and unhealthy food presentation. Kaffir lime leaf essential oil as a natural medicine can stop bacterial growth. This study aims to determine how the use of kaffir lime leaf essential oil (Citrus hystrix) has an impact on reducing the number of germs found on dining tables in restaurants in Pantai Baru Yogyakarta. This study used the True Experiment method with the Pretest Posttest with Control Group design. The research was conducted from February to April 2024. The samples used were 24 dining tables from each of the 8 restaurants, each with 3 dining tables for each restaurant. After using kaffir lime leaf essential oil spray disinfectant showed a decrease in the number of germs on the dining table at a concentration of 15% by 68.61%, a concentration of 20% by 73.76%, and a control by 53.95%. Statistical analysis shows that the use of kaffir lime leaf essential oil spray disinfectant can reduce the number of germs. The use of kaffir lime leaf essential oil (Citrus hystrix) with a concentration of 15% and 20% reduces the number of germs on the dining table at Pantai Baru restaurant in Yogyakarta.